Implementation of Clean Indoor Air Laws: Complaints, Citations, and Fines or Sanctions Related to Possible Violations of the Kansas Clean Indoor Air Act. (January 2016) - Neuberger, John S.; LaClair, Barbara
Abstract : Objective: To determine how well the Kansas Clean Indoor Air Act was being observed and enforced. Design: A survey inquired about complaints, citations, and fines or sanctions after the implementation of the Kansas Clean Indoor Air Act; inquiry was also made about the law's effectiveness. Descriptive statistics and Poisson tests of statistical significance were used. Setting: Each of the 55 Kansas cities with more than 5000 in population. Participants: Law enforcement personnel. Main Outcome Measures: Monthly rates of complaints, citations, fines or sanctions, and reports of the law's effectiveness during the 30-month period after implementation of the act. Results: Responses were received from 100% of the sampled cities. The number of citizen complaints and citations decreased over time from 4.33 to 2.42 per month and from 3.17 to 0.92 per month, respectively. The number of fines or sanctions decreased from 1.67 per month to 0.50 per month. In 51 of 55 cities (92.7%), respondents reported that the Kansas Clean Indoor Act appeared to be working effectively. There was a statistically significant difference between the first and second and first and third time periods for citations and fines or sanctions. However, there was only a statistically significant difference between the first and third time periods for citizen complaints. Conclusions: The law appears to be functioning effectively. This approach could be used to supplement measured or self-reported exposures to secondhand smoke in future studies in other jurisdictions, particularly in identifying areas with potential problems. Given the conservative nature of Kansas, adoption of such a law in the remaining states seems realistic. Abstract : This article describes a survey that inquired how well the Kansas Clean Indoor Air Act was being observed and enforced.